Reliability and concurrent validity of visual analogue scale and modified verbal rating scale of pain assessment in adult patients with knee osteoathritis in Nigeria - M. O.B Olaogun; R. A. Adedoyin; R. O. Anifaloba (AOSIS, 2003)
The objective of this study was to determine the reliability and concurrent validity of two pain rating scales - Visual Analogue Scale (VAS) and Verbal Rating Scale (VRS). The verbal rating scale was modified by translating the English description of subjective pain experience into vernacular (Yoruba) equivalents and rating the knee pain when the patient was  standing with the knee  flexed . Twenty seven patients who were clinically and radiologically diagnosed with osteoarthritis (OA) and with knee pain were purposively selected for the study. Two testers (physiotherapists) independently rated the pain experienced by patients, when bearing full weight while standing on the affected leg with slight knee flexion, over a period of several days. For each patient pain was rated with the VAS and the modified VRS (MVRS). There were significant correlations between VAS and MVRS by the same tester (tester 1 and tester2) (r=0.92, p<0.01; r = 0.89,            p<0.01respectively,)) and between VAS and MVRS between tester 1 and tester 2 (r=0.91,p<0.01). There were no significant differences between VAS for tester 1 and VAS for tester 2, and between MVRS for tester 1 and MVRS for tester 2 (p> 0.01).  According to this study, the two pain rating scales for knee OA are reliable. Our use of VAS and MVRS together with the procedure involving the flexed knee posture is, therefore, recommended for wider clinical trials.